Peran Orang Tua dan Guru Dalam Pembelajaran Talaqqi Al-Qur'ān : Studi di TPQ Al-Makmur Bandar Lor Mojoroto Kota Kediri - Aminin, Saiful (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
This article discusses the role of parents and the role of teachers in the Al-Quran learning process at TPQ Al Makmur, Kediri City. Reading the text of the Koran for children is not easy; this is because reading the Koran must be tartīl, according to the rules of tajwi>d and makha>riju al-hurūf. Parental support is important for children aged 6-7 years in learning the Koran. This study uses qualitative research with a descriptive approach. The results found that parents support the Al-Quran learning process and teachers as tutors are required to have adequate competency standards. The guidance of expert teachers of reading the Qur'an will determine the ability of TPQ students with the talaqqi> and mushafahah methods.